Antiepileptic drugs as objects of the national pharmaceutical market. Message 1. Characteristics of the nomenclature of antiepileptic drugs from the point of view of the state guarantee program of medical care of the population - Henyk, Pavlo; Levitska, Oxana; Chukhraу Iryna; Jarko, Natalia; Tereshchuk, Sophya; Hromovyk, Bohdan (Annals of Mechnikov’s Institute, 2023)
Introduction. Epilepsy, as a chronic non-infectious disease of the brain, affects according to some data about 50 million, according to others - about 65 million people worldwide. Epilepsy can be treated with antiepileptic drugs (AEDs), diet therapy, and surgery. AEDs are drugs of various origin, which are used to prevent or reduce (in intensity and frequency) seizures, their corresponding equivalents (loss or disturbance of consciousness, behavioral and autonomic disorders, etc.), which are observed during periodically occurring attacks of various forms of epilepsy. The peculiarity of the treatment of epilepsy is the need for regular daily intake of AEDs for many years, including at least 3-5 years after the cessation of seizures. The number of patients forced to take AEDs during whole life reaches 15%. Material & methods. The sources of information were: domestic and foreign web resources, the State Register of Medicines of Ukraine (for searching of AEDs) (as of February 1, 2023), registers of drugs which are subjects to reimbursement under the medical guarantee program. The several methods were used in the research, such as: information search, comparison, analysis, generalization, marketing. Results & discussion. The analytical study of AEDs showed that in Ukraine as of February 1, 2023, were registered 325 trade names (TN) of AEDs, which represented 16 international non-propriatory names (INN). About half (48.85%) of the researched assortment is made by pregabalin-based medicines. Almost one-eighth parts of the assortment (12.92% each) is taken by lamotrigine and levitiracetam TN. In total, drugs of these three INNs make up about 72% of the nomenclature of AEDs. The distribution of the studied assortment by dosage forms type showed that the absolute majority of AEDs was represented by capsules (51.08%) and tablets (45.23%). It was established that three-quarters (75.38%) of the nomenclature of AEDs are drugs of foreign production. They are represented by 65 companies from 23 countries of the world. Among them, the vast majority (88.57%) are produced by one company, a tenth part (10.20 %) – by two-three manufacturers, and three TN of Pregabalin euro (1.22 %) – by 13 enterprises. As for domestic medicines, they are represented by 13 manufacturers, and 9 out of 10 (93.75%) of their products are made by one, and the rest by two companies. High production activity regarding AEDs is characteristic of enterprises from India (16.67% of manufacturers, Index of Production Activity (IPA) = 26.28%) and Ukraine (16.67% of manufacturers, IPA = 22.96%). Among foreign enterprises, the highest production activity has Dr. Reddy’s Laboratories Limited, India (IPA = 6.63%), and among Ukrainian manufacturers - LLC "Pharma Start" (IPA = 3.83%). As a result of the data analysis of 5 Registers of medicines, the prices of which are subject to reimbursement under the program of state guarantee program of medical care of the population for 2021-2023, an increase in the number of AEDs INN from 3 to 4 was found. The analysis of the latest Register as of August 10, 2023 showed that it included 31 TN of these drugs (lamotrigine – 18, carbamazepine – 10, valproic acid – 2 and phenytoin – 1). At the same time, patients with epilepsy can receive 10 medicines free of charge, with a surcharge of up to 10% of the cost - 1 medicine, with a surcharge of 10-20% - 4 medicines, 21-30% - 10 medicines, 31-40% - 2 medicines, and in within 41-50% - 4 medicines. Conclusion. Separate components of the marketing complex regarding antiepileptic drugs registered in Ukraine and their role in the context of the program of state guarantee program of medical care of the population were studied. Keywords: Еpilepsy, antiepileptic drugs, reimbursement, Index of Production Activity